Integrated analysis of stem cell-related genes shared between type 2 diabetes mellitus and sepsis - Wang, Yubo; Jiang, Xinhai; Song, Xiaohan; Ma, Zhijie; Wang, Yan (Frontiers in Chemistry, 2025)
BackgroundDiabetes-induced immune impairment and insulin resistance increase infection risk, which may progress to sepsis that further deteriorates diabetic status. Stem cell-based interventions show therapeutic potential for both diseases. This study sought to uncover common stem cell-related genes (SCRGs) between T2DM and sepsis.MethodsThe GSE15932 dataset for T2DM and GSE65682 dataset for sepsis from the Gene Expression Omnibus (GEO) were utilized to locate common differentially expressed genes (DEGs), which were then intersected with SCRGs to derive shared differentially expressed SCRGs (DE-SCRGs). The stem-cell-related biomarkers were discovered through combining functional similarity analysis, machine learning algorithms, and receiver operating characteristic (ROC) curves. Subsequently, functional enrichment analysis, immune infiltration, and single-cell analyses were conducted to investigate the potential pathways by which biomarkers regulate T2DM and sepsis. Finally, the expression of biomarkers was further verified at both transcriptional and protein levels through the establishment of an in vitro model of T2DM-sepsis.ResultsThrough a comprehensive analysis, CAPG and DDAH2 were found and those were significantly highly expressed in both T2DM and sepsis. Analysis of functional enrichment demonstrated they were implicated in “FC gamma R-mediated phagocytosis” and “Ribosome”. Immune infiltration indicated a considerable disparity in the quantity of CD8 T cells and monocytes when comparing T2DM versus control groups, as well as sepsis versus control groups. At the cellular level, notable differences in CARG expression among alpha cells, beta cells, delta cells, and pancreatic stellate cells (PSCs) were observed in the two groups being compared. At transcription and protein levels, CAPG and DDAH2 were significantly more highly expressed in the T2DM-sepsis model than in the controls. The results corroborated the bioinformatics analysis conclusions, reinforcing the study’s validity.ConclusionTwo common stem cell-related biomarkers (CAPG and DDAH2) and their common pathways between T2DM and sepsis were discovered, providing new insights for further molecular mechanism studies.